Development and biological evaluation of tuber-legume-milk protein blends - Ruiz, Victorina Mata; Florencio, Cecilia A. (1975)
Two supplementary food mixtures were developed and evaluated in this study. The CCM mix was composed of 43:43:14 parts of cassava, cowpea, and milk protein. THE CPM mix contained 43:43:14 parts of cassava, pigeonpea, and milk protein. Biological evaluation was conducted to determine the protein quality of these food mixtures. The indices used to assess the quality of protein were protein efficiency ratio (PER), true digestibility (TD), biological value (BV), and net protein utilization (NPU). The experimental and control diets fed to the rats contained 10% protein. The results revealed that the two food mixtures and milk protein were not significantly different in terms of total weigh gained by the animals, biological value, true digestibility, and net protein utilization. It was only in protein efficiency ration where milk protein was significantly better. However, these two food mixtures, although not comparable to milk in PER, exceeded the PAG minimum recommended PER value for supplementary food mixtures. The protein content of CCM mix is 26.5%. The CPM mix has 24.60% protein. The protein content of these two food mixtures exceeded the PAG minimum recommended level of protein in supplementary foods of at least 20%. Compared to the FAO reference pattern, the amino acid content of both mixes exceeded the FAO standard for all the amino acids considered except total sulfur-containing amino acids. The biological value of the two food mixtures compared favorably with protein food mixtures developed locally and those formulated in foreign countries, such as CSM.
Mimeographed.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Proteins; Cassava as food; Legumes as food; Milk proteins